Determinants of inflation in Singapore. - Lim, Cher Siong. (2012)
The purpose of this paper is to find out the determinants of Singapore’s inflation rate using the AD/AS framework. The period of analysis is from 1980 to 2010. This paper consists of two parts, namely a qualitative and a quantitative analysis. Our results indicate that energy prices and loans and advances are positively correlated to inflation, while nominal earnings and the exchange rate are negatively correlated to inflation. While the result obtained for nominal wages is peculiar, it could have been due to CPF contributions that restrict actual consumption of the population.